Ventral simultanagnosia and prosopagnosia for unfamiliar faces due to a right posterior superior temporal sulcus and angular gyrus lesion. - Sakurai, Yasuhisa; Hamada, Kensuke; Tsugawa, Naoya; Sugimoto, Izumi (Neurocase (Taylor & Francis Ltd), 2016)
We report a patient with ventral simultanagnosia, prosopagnosia for “unfamiliar faces” (dorsal prosopagnosia), spatial agraphia, and constructional disorder, particularly on the left spatial side, due to a lesion in the right posterior superior and middle temporal gyri and angular gyrus. The patient showed impairment of fundamental visual and visuospatial recognition, such as in object size, configuration, and horizontal point location, which probably underlay the mechanism of simultanagnosia and prosopagnosia. This case also suggests that the coexistence of simultanagnosia and prosopagnosia results from a right hemispheric insult, and damage to the temporoparietal area interrupts the incorporation of spatial information into object recognition. This disconnection of information flow, together with impaired object recognition per se, may impair the parallel processing of multiple objects, leading to object-by-object or part-by-part recognition.